Classification of Production Machine Spare Part Stock Data Request Needs Using The K-Nearest Neighbor Method - Yansyah, Hamdi; Fauziah, Sifa; Maulana, Donny (International Journal Software Engineering and Computer Science (IJSECS), 2023)
Spare parts encompass various items that are offered, owned, utilized, or consumed to fulfill consumer desires and requirements. This research implements the K-Nearest Neighbor algorithm on a test dataset consisting of 100 data objects, resulting in a novel classification perspective. The study includes a comprehensive model evaluation process involving Cross Validation on both training and testing datasets, comprising 1000 records with 36 critical and 64 non-critical outcomes. Performance assessment and testing utilizing the RapidMiner Studio application yield optimal results under various modeled scenarios. The accuracy of this algorithm model stands at 98.00%, with a standard deviation of +/- 4.00%.